Factors associated with frailty among older adults attending a rural public primary care clinic in Malaysia - Ismail, Mohd Khairul Anwar; Sazlina, Shariff-Ghazali; Jahn Kassim, Puteri Shanaz (Universiti Putra Malaysia, 2023)
Introduction: Frailty is a condition occurring in older age with a reduction in homeostatic reserve and inability to react against external stressors. This resulted in falls, disability, loss of independence and mortality. At present, there are limited studies on frailty in the rural settings in Malaysia. We aimed to determine the proportion of frailty and the factors associated with frailty among older adults attending a rural clinic in Selangor. Methods: A cross-sectional study involving older adults aged >60 years who attended a rural public healthcare clinic were recruited from February-April 2018 using a systematic random sampling method. Face-to-face interview using structured pretested questionnaires and physical assessment was conducted. Data collected included socio-demography, frailty status, functional status, cognitive function, self-reported chronic diseases and polypharmacy. All analyses were done using SPSS software version 22.0. Results: The response rate was 93% with 250 participants. A total of 29 (11.6%) participants were frail and 75 (30%) were pre-frail. The factors associated with pre-frail and frail among older adults were the presence of two chronic diseases or more (aOR=4.89; 95%CI=1.29, 18.51; p=0.019), presence of polypharmacy (aOR=1.97; 95%CI=1.05, 3.72; p=0.035), abnormal walking speed based on Time Up and Go test (aOR=12.80; 95%CI=4.57, 35.86; p<0.001), and dependent IADLs based on Lawton’s IADLs (aOR= 3.06; 95%CI=1.28, 7.33; p=0.012). Conclusion: Older adults attending the rural primary clinic with risk factors such as multiple chronic diseases and polypharmacy should be screened for frailty as the condition is potentially reversible if interventions are started early.